(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
In this research a comparison between the methods of estimating cointegration regression was chosen as the four methods: Ordinary Least Square Method, Fully Modified Ordinary Least Square Method, Canonical cointegrating regression Method and Dynamic Ordinary Least Square Method. It was Found that all the results of the estimation was a good and Reliable , through a practical application of the relationship between the money supply M1 and the index of consumer prices CPI in Iraq shows the estimator of the two ways Ordinary Least Square an Dynamic Least Square are the best and most Efficient . Data analysis and results were extracted through the use of software EVIEWS.7 .